1993
DOI: 10.1084/jem.177.4.937
|View full text |Cite
|
Sign up to set email alerts
|

A requirement for membrane-associated phospholipase A2 in platelet cytotoxicity activated by receptors for immunoglobulin G and complement.

Abstract: SunliitlsryPlatelets are potent antibody-and complement-dependent cytotoxic effector cells. We showed previously that a single platelet can lyse a target cell sensitized with immunoglobulin G (IgG) and complement components up to C3 (C,,o3b denotes the target cell-bound fragment of complement up to C3; the precise nature of the bound C3 fragment has not been established), and that the complete cytotoxic system capable of specific recognition and lysis resides in platelet membranes. To define the components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…es irreversible inhibition by binding covalendy to a histidyl residue at the active site (21). pase A2 by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…es irreversible inhibition by binding covalendy to a histidyl residue at the active site (21). pase A2 by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The various lipids were preincubated with the NK cells for 1 h on ice to avoid metabolism of the Whalen/Doshi/Bader/Bankhurst added lipids [25]. Unincorporated lipid was removed prior to the cytotoxicity assay by two washes.…”
Section: Incorporation Of Exogenous Lipids Into Nk Cellsmentioning
confidence: 99%
“…Another association of complement and PLA2 has emerged from the recent description of the requirement for membraneassociated PLA2 in platelet cytotoxicity induced by receptors for IgG and complement [60]; however, neither the type of PLA2 involved in this reaction nor the precise nature of the bound C3 fragment has been characterized, although it has been shown that the complete cytotoxic system may exist as a preformed complex in platelet membranes.…”
Section: Discussionmentioning
confidence: 99%